Comparison of two vessel-sealing devices for laparoscopic-assisted ovariohysterectomy in dogs - Heblinski, Nikola; Brückner, Michael (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2018)
Objective: The study aimed to compare two different vessel-sealing devices (VSD) for laparoscopic-assisted ovariohysterectomy in dogs. Material and methods: In this randomized, prospective clinical trial 12 consecutive, client-owned, healthy, intact female dogs of different breeds were included. The dogs had been admitted for elective laparoscopic-assisted ovariohysterectomy and were randomly assigned to one of two treatment groups. The LigaSure™ was used in one group (n = 6), and the other group was operated using the Caiman® (n = 6). Recorded variables were duration of all surgical steps, number of seals required for transection of each ovarian pedicle, number of previous uses of the VSD, and complications related to each VSD. Results: Transection of the ovarian pedicles using the Caiman® required significantly fewer seals per ovary. However, overall surgical time was not significantly reduced. Intraoperative hemorrhage occurred in both groups but was more common in the LigaSure™ group. Emergency conversion to laparotomy was not required in any case. Conclusion and clinical relevance: The Caiman® can be safely used for laparoscopic-assisted ovariohysterectomy in dogs. In comparison with the Liga Sure™, the Caiman® requires fewer seals to transect ovarian pedicles, owing to the advantages of a longer working length and the first-tip closure mechanism.
Keywords: Laparoscopy; minimally invasive surgery; castration